Journeys into hybrid terrain: the case of Tara Expeditions - Thümler, Ekkehard; Beller, Annelie; Troublé, Romain (Social Science Research Network, 2014)
While considerable research on hybrid organisations has been carried out in recent years, implications for the management of hybrid nonprofits remain poorly understood. This article presents a case study on Tara Expeditions, an organisation combining scientific and civil society logics. Analysing the particular combination of advantages and challenges which is a result of hybridity, we find that a strategy of 'aggregation' is best suited to address these challenges without compromising key organizational strengths.
Gesehen am 03.02.2020